Parental metal exposures as potential risk factors for spina bifida in Bangladesh. (December 2021) - Tindula, Gwen; Mukherjee, Sudipta Kumer; Ekramullah, Sheikh Muhammad; Arman, D.M.; Biswas, Subrata Kumar; Islam, Joynul; Obrycki, John F.; Christiani, David C.; Liang, Liming; Warf, Benjamin C.; Mazumdar, Maitreyi
Highlights: Limited human research explores parental metal levels and neural tube defect risk. Our novel study examined the relationship using 18 metals measured in both parents. Maternal toenail Se and Zn were associated with spina bifida in adjusted models. Elevated paternal metals (i.e. As, Fe, and Se) were linked to spina bifida in infants. Research that examines interventions that target paternal exposure is needed. Abstract: Background: Neural tube defects are a pressing public health concern despite advances in prevention from folic acid-based strategies. Numerous chemicals, in particular arsenic, have been associated with neural tube defects in animal models and could influence risk in humans. Objectives: We investigated the relationship between parental exposure to arsenic and 17 metals and risk of neural tube defects (myelomeningocele and meningocele) in a case control study in Bangladesh. Methods: Exposure assessment included analysis of maternal and paternal toenail samples using inductively coupled plasma mass spectrometry (ICP-MS). A total of 278 participants (155 cases and 123 controls) with data collected from 2016 to 2020 were included in the analysis. Results: In the paternal models, a one-unit increase in the natural logarithm of paternal toenail arsenic was associated with a 74% (odds ratio: 1.74, 95% confidence interval: 1.26–2.42) greater odds of having a child with spina bifida, after adjusting for relevant covariates. Additionally, paternal exposure to aluminum, cobalt, chromium, iron, selenium, and vanadium was associated with increased odds of having a child with spina bifida in the adjusted models. In the maternal models, a one-unit increase in the natural logarithm of maternal toenail selenium and zinc levels was related to a 382% greater (odds ratio: 4.82, 95% confidence interval: 1.32–17.60) and 89% lower (odds ratio: 0.11, 95% confidence interval: 0.03–0.42) odds of having a child with spina bifida in the adjusted models, respectively. Results did not suggest an interaction between parental toenail metals and maternal serum folate. Discussion: Parental toenail levels of numerous metals were associated with increased risk of spina bifida in Bangladeshi infants. Paternal arsenic exposure was positively associated with neural tube defects in children and is of particular concern given the widespread arsenic poisoning of groundwater resources in Bangladesh and the lack of nutritional interventions aimed to mitigate paternal arsenic exposure. The findings add to the growing body of literature of the impact of metals, especially paternal environmental factors, on child health.